Anaerobic Nitrogen Removal: The start-up of an Anammox Reactor with pre-treated Real wastewater from the Anaerobic Digestion of municipal solid waste - Bernardo, Tiago Emanuel do Espírito Santo (2018)
In this study, wastewater produced by the Anaerobic Digestion of municipal solid waste and pre-treated by partial-nitrification was fed to a granular Anammox reactor. A conservative exponential Law was used to slowly replace the synthetic wastewater for the pre-treated wastewater, starting at 10%. This strategy was adopted in order to avoid stressful conditions to bacteria, which could thus acclimate to the reactor conditions. The experiment was divided in two phases, the first one with increasing real wastewater ratio and a second phase totally fed with real wastewater. The influent is characterized by a nitrogen loading rate of 1.5gNL-1d-1, with a NO2-N/NH4-N ratio of 1.20. Removal efficiencies were stable during all experiment, around 90%. The Anammox activity also increased during the experimentation. The Volatile suspended solids grown during phase 1 of experiment, with an initial value of 4,2 gVSSL-1. The kinetics assay results also helped checking out the removal rates for ammonium and nitrite, and production rates for nitrate. On the average the specific nitrate and ammonium removal rate, with continues NLR was 0,370,07 g NO2-N gVSS-1d-1 and 0,270,07 gNH4-N/gVSS-1d-1, respectively. For nitrate production was 0,0550,030 gNO3-NgVSS-1d-1, The organic carbon removal was also tested. The effluent values were variable, and real wastewater had no direct effect on the capability of the Anammox process to remove organic carbon. This is due to a perfect partial-nitrification, who allowed the real effluent to have low organic carbon, which not developed inhibition effect to the Anammox bacteria. During phase 2, the reactor was fed with real wastewater without any pre-treatment. This experiment wasn’t very successful, and Anammox system failed. After, was again fed with synthetic wastewater and the bacteria could recover. Results showed that the process can work with this type of wastewater, if a conservative start-up strategy is adopted and a partial-nitrification step is used to remove organic carbon.